PENGELOLAAN SUNGAI OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DI KOTA BANJARMASIN : River Management by The Department of Public Works and Spatial Planning of The City of Banjarmasin - Shofwan Alfi Maulana; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2026)
Rivers constitute an important natural resource in fulfilling the needs of society. The City of Banjarmasin is widely known as the “City of a Thousands Rivers.” The Banjarmasin Government, through the Department of Public Works and Spatial Planning, plays a role in implementing river management regulation which is Banjarmasin City Regional Regulation Number 12 of 2016. The research problem in this study is whether river management has been carried out in accordance with Banjarmasin City Regional Regulation Number 15 of 2016 on Efforts to Improve River Management. This study employs a normative juridical method, using secondary and primary data. The research is descriptive, analyzed qualitatively, and conclusions are drawn through deductive reasoning. The result indicate that the implementation of river management has not been carried out optimally due to limited resources, weak coordination among municipal agencies, and low public legal awareness in utilizing rivers. Therefore, stronger coordination agency, effective law enforcement, and active community participation are required to improve river management.